Selective Decontamination of the Digestive Tract Reduces Pneumonia and Mortality - Lenneke E. M. Haas; Marcus J. Schultz (Critical Care Research and Practice)
Selective decontamination of the digestive tract (SDD) has been subject of numerous randomized controlled trials in critically ill patients. Almost all clinical trials showed SDD to prevent pneumonia. Nevertheless, SDD has remained a controversial strategy. One reason for why clinicians remained reluctant to implement SDD into daily practice could be that mortality was reduced in only 2 trials. Another reason could be the heterogeneity of trials of SDD. Indeed, many different prophylactic antimicrobial regimes were tested, and dissimilar diagnostic criteria for pneumonia were applied amongst the trials. This heterogeneity impeded interpretation and comparison of trial results. Two other hampering factors for implementation of SDD have been concerns over the risk of antimicrobial resistance and fear for escalation of costs associated with the use of prophylactic antimicrobials. This paper describes the concept of SDD, summarizes the results of published trials of SDD in mixed medical-surgical intensive care units, and rationalizes the risk of antimicrobial resistance and rise of costs associated with this potentially life-saving preventive strategy.